Case report: Transcatheter arterial embolization in a newborn with cervical rapidly involuting congenital hemangioma and Kasabach–Merritt phenomenon - Peng, Ying-Hsuan; Lin, Ming-Chih; Liu, Wei-Li; Jan, Sheng-Ling (Frontiers in Pediatrics, 2023)
Congenital hemangiomas (CHs) are rare vascular tumors and do not exhibit progressive postnatal growth. The incidence is less than 3% of all hemangiomas. Most CHs have a favorable prognosis; however, the Kasabach–Merritt phenomenon (KMP) is a rare but life-threatening complication in CHs that requires aggressive treatment. Medical treatments with corticosteroids and interferon have been suggested. Surgical resection can be considered for the treatment of complicated CHs in medically resistant lesions. Vascular embolization could be an alternative method if surgery is not considered feasible. Herein, we report a case of a 9-day-old newborn who underwent arterial embolization for a CH with KMP, combined with sirolimus treatment, and the outcome was favorable. The hemangioma completely regressed by 3 months and rapidly involuting congenital hemangioma (RICH) was diagnosed. Our successful experience with treating RICH associated with KMP revealed that RICH can have potentially serious complications although they usually resolve rapidly after birth without treatment. Surgical resection is considered to be the standard method for the treatment of medically resistant vascular tumors, but it is difficult to perform during the active phase of KMP due to acute bleeding and severe coagulopathy. Arterial embolization is feasible and can be used as an alternative to surgical resection, even in small babies.